The effect of biochar-compost mixture on oil palm seedling growth performance and nutrients uptake / Mohd Shaufi Mohamad Tahar - Mohamad Tahar, Mohd Shaufi (Faculty of Plantation and Agrotechnology, 2018)
A glasshouse study was conducted to investigate the effects of mixture EFB biochar and EFB compost as growth medium on oil palm seedlings growth. There were four treatments with three replications consists of different volume of topsoil, EFB compost and EFB biochar ranging from 5% - 100%. The result showed treatment 3 with 25% EFB compost and 5% EFB biochar are the best rate on oil palm seedling growth as it is significant for the plant height, number of leaf, and chlorophyll content. For leaf number, treatment three is 100% higher from treatment one. For plant height, treatment three is 22.27% higher than treatment one with different 10.6cm. For chlorophyll content, treatment three is 3.88% higher than treatment one with different 1.9 in average. There is also a different of macronutrient content within different treatment.